Female CFOs, Earnings Quality, and the Cost of Capital: Evidence from Indonesian Listed Firms (2015–2024) - Jubery Marwan; Meiliyah Ariani; Aji Yoga Sekar (Goodwood Publishing, 2025)
This study examines whether female chief financial officers (CFOs) improve earnings quality and reduce the cost of capital in Indonesian listed firms, and whether earnings quality mediates the relationship between female CFO presence and financing costs. Using an unbalanced firm-year panel of non-financial companies listed on the Indonesia Stock Exchange for 2015–2024, the analysis employs fixed-effects regressions with year effects to control for unobserved time-invariant firm heterogeneity and common macro shocks. Earnings quality is primarily measured using accrual quality based on the Dechow–Dichev accrual estimation error framework, with absolute discretionary accruals as a robustness proxy. The cost of capital is operationalized using the cost of equity (CAPM-based), cost of debt, and an integrated measure (WACC). Results indicate that female CFO presence is associated with significantly higher earnings quality, reflected in lower accrual estimation error and lower absolute discretionary accruals. Consistent with information-risk pricing, poorer earnings quality is positively associated with higher costs of equity, debt, and overall capital. Mediation tests using bootstrap confidence intervals show that earnings quality partially mediates the relationship between female CFO presence and the cost of capital, while a remaining direct effect, particularly for equity-related outcomes, suggests an additional governance credibility or signaling channel beyond accounting-based earnings-quality measures. Robustness checks using alternative standard error structures, alternative earnings-quality proxies, and lagged specifications yield consistent inferences. Overall, the findings highlight the CFO as a micro-foundation of reporting credibility and suggest that financial leadership and reporting discipline can function as a cost-of-capital strategy in emerging markets characterized by heterogeneous disclosure and concentrated ownership.